Serious Games and Gamification for Mental Health: Current Status and Promising Directions - Fleming, Theresa M.; Bavin, Lynda; Stasiak, Karolina; Hermansson-Webb, Eve; Merry, Sally N.; Cheek, Colleen; Lucassen, Mathijs; Lau, Ho Ming; Pollmuller, Britta; Hetrick, Sarah (Frontiers in Psychiatry, 2017)
Computer games are ubiquitous and can be utilised for serious purposes such as health and education. ‘Applied games’ including serious games (in brief, computerised games for serious purposes) and gamification (gaming elements used outside of games) have the potential to increase the impact of mental health internet interventions via three processes. Firstly, by extending the reach of online programs to those who might not otherwise use them. Secondly, by improving engagement through both game-based and ‘serious’ motivational dynamics. Thirdly, by utilising varied mechanisms for change, including therapeutic processes and gaming features. In this scoping review, we aim to advance the field by exploring the potential and opportunities available in this area. We review engagement factors which may be exploited and demonstrate that there is promising evidence of effectiveness for serious games for depression from contemporary systematic reviews. We illustrate six major categories of tested applied games for mental health (exergames, virtual reality, CBT based serious games and gamification, entertainment games, biofeedback and cognitive training games) and demonstrate that it is feasible to translate traditional evidence-based interventions into computer gaming formats and to exploit features of computer games for therapeutic change. Serious games and gamification have considerable potential for increasing the impact of online interventions for mental health. However, there are few independent trials and direct comparisons of game-based and non-game-based interventions are lacking. Further research, faster iterations, rapid testing, non-traditional collaborations, and user-centred approaches are needed to respond to diverse user needs and preferences in rapidly changing environments.